Implementation of the Smart Indonesia Card Scholarship (KIP) Acceptance Using the K-NN Method (Case Study: Politeknik Siber Cerdika Internasional) - Abi Surya Wijaya; Lena Magdalena; Chairun Nas (Publikasi Indonesia, 2024)
This study discusses the implementation of the K-Nearest Neighbor (K-NN) method in the process of receiving the Smart Indonesia Card (KIP) scholarship at the Cerdika International Cyber Polytechnic. The main purpose of this study is to improve accuracy and efficiency in the selection of KIP scholarship recipients. The K-NN method was chosen because of its ability to classify data based on the proximity of features between samples. This research involves analyzing data on prospective scholarship recipients which includes variables such as academic achievement, economic conditions, and extracurricular activities. The results of the implementation of the K-NN method show that this method can be used as an effective tool in the selection process of KIP scholarship recipients, with a fairly high level of accuracy compared to traditional methods. This finding is expected to help the Polytechnic in increasing transparency and fairness in providing scholarships.